Molecular Mechanisms of Herbicide Resistance. Issue Volume 63: Issue SP1(2015) (February 2015) - Délye, Christophe; Duhoux, Arnaud; Pernin, Fanny; Riggins, Chance W.; Tranel, Patrick J.
Abstract : Resistance to herbicides occurs in weeds as the result of evolutionary adaptation (Jasieniuk et al. 1996). Basically, two types of mechanisms are involved in resistance (Beckie and Tardif 2012; Délye 2013). Target-site resistance (TSR) is caused by changes in the tridimensional structure of the herbicide target protein that decrease herbicide binding, or by increased activity (e.g., due to increased expression or increased intrinsic activity) of the target protein. Nontarget-site resistance (NTSR) is endowed by any mechanism not belonging to TSR, e.g., reduction in herbicide uptake or translocation in the plant, or enhanced herbicide detoxification (reviewed in Délye 2013; Yuan et al. 2007).